Persona humana, corazón de la paz: Mensaje de Benedicto XVI en la Jornada Mundial de la Paz, 1 de enero de 2007 - Corral, Carlos; Alonso, Antonio (UNISCI Discussion Papers, 2007)
The Message for the 2007 World Day of Peace is focused on the human person, as a rational being like God. For keeping peace, the human being must therefore discover the natural rules for the relations between the human family and the world, and among humans themselves, and put them in practice. In the international stage, it specifically condemns war, and warns about some of the possible consequences of conflicts (inequalities, resource scarcity, terrorism...), mentioning the counflict in the south of Lebanon. It concludes with an invitation for becoming a “peace builder”.